Histone Demethylases Coordinate the Antagonistic Interaction Between Abscisic Acid and Brassinosteroid Signaling in Arabidopsis - Wu, Jinfeng; Yan, Mingli; Zhang, Dawei; Zhou, Dinggang; Yamaguchi, Nobutoshi; Ito, Toshiro (Frontiers in Plant Science, 2020)
Abscisic acid (ABA) interacts antagonistically with brassinosteroids (BRs) to control plant growth and development in response to stress. The response to environmental cues includes hormonal control via epigenetic regulation of gene expression. However, the details of the ABA–BR crosstalk remain largely unknown. Here, we show that JUMONJI-C domain containing histone demethylases (JMJs) coordinate the antagonistic interaction between ABA and BR signaling pathways during the post-germination stage in Arabidopsis. BR blocks ABA-mediated seedling arrest through repression of JMJ30. JMJs remove the repressive histone marks from the BRASSINAZOLE RESISTANT1 (BZR1) locus for its activation to balance ABA and BR signaling pathways. JMJs and BZR1 co-regulate genes encoding three membrane proteins, a regulator of vacuole morphology, and two lipid-transfer proteins, each of which play a different role in transport. BZR1 also regulates stimuli-related target genes in a JMJ-independent pathway. Our findings suggest that the histone demethylases integrate ABA and BR signals, leading to changes in growth program after germination.